Ottoman foundation libraries in the age of reform: The final period - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2004)
With the inauguration of institutional reforms in the second half of the nineteenth century, the classical Ottoman library system, which had served Ottoman society and the educational infrastructure successfully for many centuries became increasingly obsolete as the new type of library began to appear. Towards the end of the nineteenth century and into the twentieth century complaints about the conditions of foundation libraries markedly increased. Some attempts to redress the causes for the complaints were made, but these were generally unsuccessful. By the beginning of the twentieth century, these libraries had become institutions serving researchers in the field of Islamic culture and the occasional student pursuing the classical curriculum at the Islamic colleges. This article will trace the gradual process of these libraries to obsolescence and will attempt to discover the causes.